Display panel and display device

By using additives with low surface energy in the display panel to form a raised interface, and combining the layer with the hardened layer to enhance the bonding strength, the problem of insufficient bonding strength of the liquid-liquid interface in the flexible display device is solved, and the packaging is improved Sealing and stability.

CN119200288APending Publication Date: 2024-12-27SHANGHAI TIANMA MICRO ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573235.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The liquid-liquid interface bonding strength of the existing flexible display devices is insufficient, resulting in complex packaging structure and unweather resistance, affecting the stability and usability of the display screen.

Method used

The first additive with a surface energy lower than that of the electrophoretic medium is introduced into the display panel, so that the electrophoretic medium forms an interface protruding in the direction of the sealing layer, increases the contact area between the sealing layer and the cofferdam, and enhances the liquid-liquid interface through the bonding layer and the hardening layer bond strength.

Benefits of technology

The bonding strength between the sealing layer and the cofferdam and the sealing property of the liquid-liquid interface are improved, and the sealing property and stability of the flexible packaging are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200288A_ABST
    Figure CN119200288A_ABST
Patent Text Reader

Abstract

The invention provides a display panel and a display device. The display panel comprises a first substrate and a second substrate which are oppositely arranged; the electrophoretic display layer is positioned between the first substrate and the second substrate; the electrophoretic display layer comprises a cofferdam and a containing cavity defined by the cofferdam, and an electrophoretic medium is arranged in the containing cavity; the sealing layer is positioned between the electrophoretic display layer and the second substrate; wherein the electrophoretic medium comprises a first additive, and the surface energy of the first additive is smaller than that of the electrophoretic medium. The adhesive force of the sealing layer to the cofferdam is increased, the bonding strength of liquid-liquid interface contact is improved, and the sealing performance of flexible packaging is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic electroluminescence, and in particular relates to a display panel and a display device. Background Art

[0002] Electronic Paper Display (EPD) is a thin and light display screen that is energy-saving, environmentally friendly, has good contrast, and is easy to process. As early as the 1970s, electrophoretic display technology was first reported. However, at the end of the 20th century, the microcapsule packaging technology used by E-Ink Company in the United States greatly promoted the industrialization of electronic paper displays.

[0003] Existing flexible display devices all have certain bending properties, the bonding strength of the liquid-liquid interface contact is insufficient, and the bonding force of the adhesive to the cofferdam is weak, so the weather resistance of the flexible package cannot be achieved, which affects the stability and usability of the display.

[0004] Therefore, the liquid-liquid interface bonding strength of the existing flexible packaging is insufficient and the packaging structure is relatively complex. Summary of the invention

[0005] The purpose of the present application is to provide a display panel and a display device. The display panel of the present application can increase the adhesion of the sealing layer to the cofferdam, improve the bonding strength of the liquid-liquid interface contact, and help improve the sealing of the flexible package.

[0006] In a first aspect, an embodiment of the present application provides a display panel, comprising: a first substrate and a second substrate arranged opposite to each other; an electrophoretic display layer located between the first substrate and the second substrate; the electrophoretic display layer comprising a cofferdam and a receiving cavity defined by the cofferdam, wherein an electrophoretic medium is arranged in the receiving cavity; a sealing layer located between the electrophoretic display layer and the first substrate; wherein the electrophoretic medium contains a first additive, and the surface energy of the first additive is less than the surface energy of the electrophoretic medium.

[0007] In some embodiments, the electrophoretic medium forms an interface that bulges toward the sealing layer.

[0008] In some embodiments, the surface energy of the first additive is less than 25 mN / m.

[0009] In some embodiments, the first additive is a hydrophobic material, and the mass percentage of the hydrophobic material in the electrophoretic medium is 0.01% to 1%.

[0010] In some embodiments, it also includes: a bonding layer located between the electrophoretic medium and the sealing layer; the electrophoretic medium contains a second additive, the sealing layer includes a third additive, the bonding layer is formed by the reaction of the second additive and the third additive, and the bonding layer is located on the surface of the sealing layer close to the electrophoretic display layer.

[0011] In some embodiments, the second additive includes a silicon-containing compound, the third additive includes a silane coupling agent, and the bonding layer has a Si—O—Si chemical bond.

[0012] In some embodiments, the chemical formula of the silicon-containing compound is as shown in Formula I below:

[0013]

[0014] In Formula I, X represents a hydrolyzable group, and R1 is selected from active groups capable of interacting with an organic resin;

[0015] The general chemical formula of the silane coupling agent is R2-Si(OM)3, wherein R2 is selected from an organic group and OM represents a hydrolyzable alkoxy group.

[0016] In some embodiments, X is selected from a halogen atom, an alkoxy group, and an acyloxy group; R1 is selected from at least one of an amino group, a thiol group, a vinyl group, an epoxy group, a cyano group, and a methylacryloxy group; and R2 is selected from at least one of an amino group, a vinyl group, a methyl group, an epoxy group, a thiol group, and an acryloxypropyl group.

[0017] In some embodiments, the mass percentage of the second additive in the electrophoretic medium is 0.01% to 1%, and the mass percentage of the third additive in the sealing layer is 0.05% to 1%.

[0018] In some embodiments, it also includes: a hardening layer, located between the electrophoretic medium and the sealing layer; the electrophoretic medium contains a fourth additive, the density of the fourth additive is lower than the density of the electrophoretic medium, the hardening layer is formed by a cross-linking reaction between the fourth additive and the sealing layer, and the hardening layer is located on the surface of the sealing layer close to the electrophoretic display layer.

[0019] In some embodiments, the fourth additive has a first active group, the adhesive used to form the sealing layer has a second active group, and the first active group and the second active group are independently selected from at least one of a carbon-carbon double bond, a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an aldehyde group, and a halogenated alkyl group.

[0020] In some embodiments, the fourth additive includes a multifunctional acrylic monomer having a density below 1.2 g / mL.

[0021] In some embodiments, the multifunctional acrylic monomer includes at least one of ethylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, triethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and pentaerythritol triacrylate; and the sealing layer includes polyacrylate and / or polymethacrylate.

[0022] In some embodiments, the hardened layer has intermolecular hydrogen bonds.

[0023] In some embodiments, the material of the cofferdam and the first substrate is a polymer having polar groups, and the sealing layer is connected to the cofferdam and the first substrate through a dipole effect.

[0024] In some embodiments, the Shore hardness of the hardened layer is greater than 50 HA.

[0025] In some embodiments, within the scope of a single accommodating cavity defined by the cofferdam, an angle between the sealing layer that seals the accommodating cavity and a side wall of the cofferdam is less than 90°.

[0026] In some embodiments, within the scope of a single accommodating cavity defined by the cofferdam, an edge thickness H1 of the sealing layer that seals the accommodating cavity and a middle thickness H2 of the sealing layer satisfy: 1 ​​nm ≤ H1 - H2 ≤ 100 nm.

[0027] In some embodiments, an orthographic projection area of ​​a top surface of the cofferdam away from the second substrate on the second substrate is larger than an orthographic projection area of ​​a bottom surface of the cofferdam close to the second substrate on the first substrate.

[0028] In a second aspect, an embodiment of the present application provides a display device, comprising the display panel described in the first aspect.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] In the display panel of the present invention, the electrophoretic medium contains a first additive, and the surface energy of the first additive is smaller than the surface energy of the electrophoretic medium. Under the action of the first additive, the surface of the electrophoretic medium forms an interface with a middle convexity, and the electrophoretic medium forms an interface convex toward the sealing layer, so that the contact area between the sealing layer and the cofferdam is increased, thereby improving the bonding strength between the sealing layer and the cofferdam, and improving the bonding strength of the liquid-liquid interface contact, which is beneficial to improving the sealing of the flexible package. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0032] Figure 1 A schematic diagram of the exploded structure of a display panel provided in an embodiment of the present application;

[0033] Figure 2 A schematic diagram of the structure of a display panel provided in Embodiment 1 of the present application;

[0034] Figure 3 A schematic diagram of the structure of another display panel provided in the second embodiment of the present application;

[0035] Figure 4 A schematic diagram of the packaging state of the display panel provided in the second embodiment of the present application;

[0036] Figure 5 A schematic diagram of the structure of another display panel provided in the third embodiment of the present application;

[0037] Figure 6a A schematic diagram of hydrogen bonding between a sealing layer and an electrophoretic medium in a display panel provided in an embodiment of the present application;

[0038] Figure 6b A schematic diagram of a dipole connection between a sealing layer and a first substrate in a display panel provided in an embodiment of the present application;

[0039] Figure 7 A schematic diagram of the structure of another display panel provided in the fourth embodiment of the present application;

[0040] Figure 8a A schematic diagram of the structure of another display panel provided in Embodiment 5 of the present application;

[0041] Figure 8b A cross-sectional transmission electron microscope image of another display panel provided in Example 5 of the present application;

[0042] Fig. 9 A schematic diagram of the structure of a display device provided in an embodiment of the present application. DETAILED DESCRIPTION

[0043] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0044] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0045] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0046] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0047] Existing flexible electrophoretic display panels have certain bending properties, the bonding strength of the liquid-liquid interface contact is insufficient, the adhesive's bonding force to the cofferdam is weak, and the weather resistance of the flexible package cannot be achieved, which affects the stability and usability of the display.

[0048] Therefore, the liquid-liquid interface bonding strength of the existing flexible packaging is insufficient and the packaging structure is relatively complex. Figure 1 The following is a schematic diagram of the exploded structure of a display panel provided in an embodiment of the present application. Figure 1 As shown, an embodiment of the present application provides a display panel, including: a first substrate 10 and a second substrate 40 arranged opposite to each other; an electrophoretic display layer 20 located between the first substrate 10 and the second substrate 40; the electrophoretic display layer 20 includes a cofferdam and a receiving cavity defined by the cofferdam, and an electrophoretic medium is arranged in the receiving cavity; a sealing layer 30 located between the electrophoretic display layer 20 and the first substrate 10.

[0049] like Figure 1 As shown, the first substrate 10 may be a substrate having light transmittance and flexibility such as an insulating synthetic resin, for example, a hard substrate such as a glass substrate, a plastic substrate, etc., or a flexible substrate such as a PET film substrate, etc. The first substrate 10 has a display surface, which may be a surface of the first substrate 10 away from the second substrate 40.

[0050] In the present application, the first substrate 10 is a transparent substrate, which can be made of materials such as polyethylene terephthalate (PET), polyethylene (PE), polyimide (PI), polyethylene naphthalate (PEN), etc. A first electrode 11 is formed on the surface of the first substrate 10 close to the electrophoretic display layer 20. The first electrode 11 can be an indium tin oxide (ITO) film, a nanosilver wire, or a graphene film, etc. The first electrode 11 can be arranged in an array on the surface of the first substrate 10.

[0051] The second substrate 40 is arranged relative to the first substrate 10 and spaced apart from each other. The second substrate 40 may also be a flexible substrate formed of resin, or a hard substrate formed of glass, plastic, etc. The second substrate 40 may be used as a carrier to carry other film structures in the display device. A second electrode 41 is formed on the surface of the second substrate 40 close to the electrophoretic display layer 20. The second electrode 41 may be arranged in an array to drive the electrophoretic medium 22 to form an image.

[0052] The first substrate 10 and the second substrate 40 are both provided with electrodes for applying electrical signals on both sides of the electrophoretic display layer 20. The second electrode may be a pixel electrode of the display panel, and the display of the electrophoretic display layer 20 is controlled by controlling the voltage signal on the driving electrode through the controller.

[0053] Figure 2 This is a schematic diagram of the structure of the display panel provided in the first embodiment of the present application, such as Figure 2 As shown, the electrophoretic display layer 20 includes a cofferdam 21 and a receiving cavity defined by the cofferdam, and an electrophoretic medium 22 is arranged in the receiving cavity. The electrophoretic medium 22 includes an electrophoretic liquid and electrophoretic particles distributed in the electrophoretic liquid. The electrophoretic particles are the main components used in the display panel to achieve the display effect. The electrophoretic particles can be spherical, square, polygonal or other irregular shapes, which is not limited in the embodiment of the present application. The multiple first electrodes 11 and the multiple second electrodes 41 form a pulsed electric field to drive the electrophoretic particles to rotate.

[0054] The thickness of the electrophoretic display layer 20 is specifically 10 to 1000 μm, and can be specifically 10 μm, 50 μm, 100 μm, 300 μm, 500 μm, 600 μm, 800 μm or 1000 μm, and can be other values ​​within the above range, which are not limited here. The thickness of the electrophoretic display layer 20 can be further specifically 50 to 800 μm, and further can be 50 to 500 μm.

[0055] The sealing layer 30 is used to seal the accommodating cavity formed by the cofferdam 21. The material of the sealing layer 30 can be an adhesive. The adhesive includes oligomers or polymers containing crosslinkable groups such as acrylate or its derivatives, epoxy resin, epoxy resin derivatives, and resin monomers. The above adhesive material forms a sealing layer after thermal radiation, photocuring, etc., so that the sealing layer 30 forms a continuous film layer on the surface of the electrophoretic medium. Of course, the adhesive also includes an organic solvent, and the present application does not limit the components of the organic solvent.

[0056] In some embodiments, the adhesive includes an acrylate prepolymer, a photoinitiator, a crosslinking agent and a conductive material. In the specific preparation process, 52 parts by mass of isooctyl acrylate (EHA), 35 parts by mass of isobornyl acrylate (IBOA), 12 parts by mass of hydroxyethyl acrylate (HEA), 1 part by mass of acrylamide (AM) and 0.1 part by mass of hydroxycyclohexyl phenyl ketone are fully mixed and placed under 365nm ultraviolet light to react to a viscosity of 3500cps to obtain an acrylate prepolymer. The prepolymer is mixed with other additives (photoinitiator TPO 0.1%, crosslinking agent HDDA 0.1%, conductive material 2%) to obtain a sealing layer adhesive. Exemplarily, the conductive material can be a conductive nanomaterial, such as carbon nanotubes, nano silver wires, graphene and fullerene carbon. The conductive material can also be a conductive polymer, such as polyaniline, polypyrrole, polythiophene and polyacrylamine polymers. The conductive material can also include an antistatic agent.

[0057] In some embodiments, the coating thickness of the sealing layer 30 can be 10 to 50 μm, specifically 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. The sealing layer 30 is formed by coating the adhesive into a film, and the specific coating process can be a common method used by those skilled in the art. After coating and forming, light curing and heat curing are generally used to accelerate the forming of the sealing layer 30, and the flatness of the sealing layer can also be improved.

[0058] In some embodiments, the material of the cofferdam 21 may be a thermoplastic material or a thermosetting material, specifically, acrylate, epoxy resin, epoxy resin derivative, etc., which is not limited here.

[0059] The accommodating cavity formed by the cofferdam 21 is open at both ends, one end of which faces the first substrate 10, and the other end faces the second substrate. A sealing layer 30 is provided between the first substrate 10 and the electrophoretic display layer 20. The accommodating cavity formed by any cofferdam 21 can be a cube, a sphere, an ellipsoid, or a cone, etc., which is not limited here, as long as each accommodating cavity can accommodate the electrophoretic medium. Figure 1The structure position relationship in the display panel is only illustrated, and does not represent the actual size and shape of each layer structure.

[0060] The present application also provides a method for preparing a display panel, comprising the following steps:

[0061] Providing a first substrate 10 and a second substrate 40;

[0062] A cofferdam 21 is formed on the second substrate 40, and an electrophoretic medium is filled into a plurality of accommodating cavities of the cofferdam 21 to form an electrophoretic display layer 20;

[0063] An adhesive is coated on the electrophoretic display layer 20 , and the adhesive is cured to form a sealing layer 30 . The sealing layer 30 connects the electrophoretic display layer and the first substrate 10 . The electrophoretic medium 22 is in direct contact with the sealing layer 30 .

[0064] In some embodiments, a sealing layer 30 may be disposed between the second substrate 40 and the electrophoretic display layer 20 , so as to improve the bonding stability between the second substrate 40 and the electrophoretic display layer 20 .

[0065] In order to improve the interfacial bonding strength between the sealing layer 30 and the electrophoretic display layer, in some embodiments, the electrophoretic medium 22 includes a first additive, and the surface energy of the first additive is smaller than the surface energy of the electrophoretic medium.

[0066] In the above scheme, the electrophoretic medium of the display panel contains a first additive, and the surface energy of the first additive is smaller than the surface energy of the electrophoretic medium. Under the action of the first additive, the surface of the electrophoretic medium forms an interface with a middle convexity, and the electrophoretic medium forms an interface convex toward the sealing layer, so that the contact area between the sealing layer and the cofferdam is increased, thereby improving the bonding strength between the sealing layer and the cofferdam, and improving the bonding strength of the liquid-liquid interface contact, thereby improving the sealing strength between the sealing layer and the electrophoretic display layer, which is beneficial to improving the sealing of the flexible package.

[0067] Through transmission electron microscopy, the electrophoretic medium 22 forms an interface that bulges toward the sealing layer 30. Figure 2 Since the electrophoretic medium 22 contains the first additive with low surface energy, the first additive can migrate to the surface of the electrophoretic medium, so that the surface of the electrophoretic medium 22 forms an interface that bulges toward the sealing layer.

[0068] In some embodiments, the surface energy of the first additive is lower than 25 mN / m, and may be specifically 25 mN / m, 24 mN / m, 23 mN / m, 22 mN / m, 20 mN / m, 18 mN / m, 16 mN / m, 15 mN / m or 10 mN / m, etc. It may also be other values ​​within the above range, which is not limited here.

[0069] The surface energy of the electrophoretic medium is greater than 25 mN / m, and can be specifically 26 mN / m, 27 mN / m, 28 mN / m, 30 mN / m, 32 mN / m, 33 mN / m, 34 mN / m or 35 mN / m, etc., and can also be other values ​​within the above range, which are not limited here. Since the surface energy of the first additive is lower than the surface energy of the entire electrophoretic medium, the first additive can migrate to the surface of the electrophoretic medium, so that a raised interface is formed on the surface of the electrophoretic medium 22.

[0070] In some embodiments, the first additive is a hydrophobic material, and the mass percentage of the hydrophobic material in the electrophoretic medium is 0.01% to 1%, specifically 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Under the action of the hydrophobic material, the surface of the electrophoretic medium forms a raised interface in the middle, and the contact area between the adhesive covering the electrophoretic medium and the cofferdam becomes larger, thereby improving the bonding strength between the sealing layer and the cofferdam. In addition, the hydrophobic material in the electrophoretic medium can also play a hydrophobic role and improve the dispersion uniformity of the electrophoretic particles in the electrophoretic medium.

[0071] In some embodiments, the hydrophobic material is selected from at least one of an organosilicon hydrophobic agent, an organofluorine hydrophobic agent, a hydrocarbon hydrophobic agent, and a silicon hydrophobic agent.

[0072] Specifically, the surface tension of the organosilicon hydrophobic agent is about 20 mN / m, and the organosilicon hydrophobic agent may be a siloxane compound, sodium methyl silicate, poly (methyl hydrogen) siloxane, or the like.

[0073] The surface tension of the organic fluorine hydrophobic agent is about 18 mN / m, and specific examples include perfluorooctane sulfonic acid, perfluorooctanoic acid, fluoroalkane sulfonic acid, fluorooctane sulfonic acid, and perfluorocarbon compounds.

[0074] The surface tension of hydrocarbon hydrophobic agents is about 30 mN / m, and they may specifically be long-chain alkanes, aromatic hydrocarbons, cycloalkanes, and the like.

[0075] The silicon-based hydrophobic agent may be, for example, fluorinated nano-silicon monoxide. Preferably, the hydrophobic material comprises polydimethylsiloxane (abbreviated as PDMS).

[0076] In some embodiments, after the sealing layer 30 is peeled off from the electrophoretic display layer 20, the surface water drop angle of the sealing layer 30 close to the electrophoretic display layer 20 is 90° to 115°, specifically 90°, 100°, 105°, 110°, 112° or 120°, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Since the surface energy of the hydrophobic material is low, it will migrate to the surface of the electrophoretic medium, so part of the hydrophobic material will adhere to the surface of the sealing layer 30, so that the surface water drop angle of the sealing layer 30 can be low, which is conducive to the formation of a convex interface in the middle on the surface of the electrophoretic medium.

[0077] In some embodiments, within the scope of a single accommodating cavity defined by the cofferdam 21, the edge thickness H1 of the sealing layer 30 that seals the accommodating cavity is greater than the middle thickness H2 of the sealing layer 30. As it can be seen that the sealing layer 30 has a trend of being thin in the middle and thick at the edges, this is because a raised interface is formed in the middle on the surface of the electrophoretic medium, and the raised interface affects the structure of the sealing layer 30 formed by the adhesive.

[0078] In some embodiments, 1nm≤H1-H2≤100nm, and specifically can be 1nm, 2nm, 3nm, 4nm, 5nm, 10nm, 15nm, 20nm, 30nm, 50nm, 80nm or 100nm, etc., which is not limited here.

[0079] In some embodiments, within the scope of a single accommodating cavity defined by the cofferdam, the angle between the surface of the sealing layer that seals the accommodating cavity and the side wall of the cofferdam is less than 90°. In the present application, the encapsulated display panel can be subjected to section processing, and then a transmission electron microscope can be used to measure the angle between the sealing layer and the side wall of the cofferdam. Preferably, the angle is 10° to 60°. The sealing layer 30 of this structure can reduce the angle with the side wall of the cofferdam 21. When the first additive is not added to the electrophoretic medium, the liquid level of the electrophoretic medium is horizontal as a whole, and the thickness of the sealing layer that seals the electrophoretic medium is more uniform. The angle between the sealing layer 30 and the side wall of the cofferdam 21 is about 90°.

[0080] In some embodiments, the adhesive strength between the sealing layer 30 and the electrophoretic display layer 20 is ≥500gf / 25mm, and can be specifically 500gf / 25mm, 550gf / 25mm, 580gf / 25mm, 600gf / 25mm, 650gf / 25mm, 700gf / 25mm, etc., which is not limited here.

[0081] In some embodiments, the optical transmittance of the sealing layer is greater than 92%, and may specifically be 92.5%, 93%, 93.5%, 94%, 95%, 96%, 97%, 98% or 99%, etc., and may of course be other values ​​within the above range. Since the optical transmittance of the sealing layer is good, it will not affect the formation of images by the electrophoretic particles on the display surface of the first substrate.

[0082] Figure 3 A structural diagram of another display panel provided in the second embodiment of the present application is shown in FIG. Figure 3 As shown, the display panel further includes a bonding layer 50 located between the electrophoretic medium 22 and the sealing layer 30 . The bonding layer 50 may be located on a surface of the sealing layer 30 close to the electrophoretic display layer 20 , or may be a part of the sealing layer 30 .

[0083] Figure 4 This is a schematic diagram of the packaging state of the display panel provided in Example 2 of the present application. During the packaging process, the adhesive is coated on the surface of the electrophoretic display layer, and then the adhesive is cured by photocuring or thermal curing to form a sealing layer 30. During the photocuring or thermal curing reaction, the additives in the electrophoretic medium can chemically react with the additives in the sealing layer to form a bonding layer.

[0084] In some embodiments, the electrophoretic medium 22 includes a second additive, the sealing layer 30 includes a third additive, and the bonding layer 50 is formed by the reaction of the second additive and the third additive. Since the second additive in the electrophoretic medium can chemically react with the third additive in the sealing layer, the bonding layer formed by the chemical reaction can further enhance the interfacial bonding strength between the sealing layer and the electrophoretic display layer.

[0085] In some embodiments, the mass percentage of the second additive in the electrophoretic medium is 0.01% to 1%, specifically 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and of course, it can also be other values ​​within the above range, which is not limited here. In the present application, controlling the amount of the second additive can improve the bonding strength between the sealing layer and the electrophoretic display layer and increase the structural reliability of the display device without affecting the performance of the electrophoretic medium.

[0086] In some embodiments, the second additive includes a silicon-containing compound, and the chemical formula of the silicon-containing compound is shown in Formula I below:

[0087]

[0088] In Formula I, X represents a hydrolyzable group, and R1 is selected from active groups capable of interacting with an organic resin.

[0089] In some specific embodiments, X is selected from a halogen atom, an alkoxy group, and an acyloxy group. The halogen atom may be, for example, F, Cl, Br, I, and the like.

[0090] R1 is selected from at least one of amino, mercapto, vinyl, epoxy, cyano and methylvinyloxy groups; the R1 group can interact with the organic resin, which can be a chemical reaction or a physical adsorption, which is not limited here.

[0091] In some embodiments, the silicon-containing compound includes at least one of epoxy-amino silicone oil, amino-functional silane, γ-glycidyloxypropyltrimethoxysilane, poly(methylhydrogen)siloxane, and the like.

[0092] In some embodiments, the mass percentage of the third additive in the sealing layer is 0.05% to 1%, specifically 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. In the present application, controlling the amount of the third additive can improve the bonding strength between the sealing layer and the electrophoretic display layer and increase the structural reliability of the display device without affecting the performance of the sealing layer.

[0093] In some embodiments, the third additive includes a silane coupling agent, and the general chemical formula of the silane coupling agent is R2-Si(OM)3, wherein R2 is selected from an organic group, and OM represents a hydrolyzable alkoxy group.

[0094] Specifically, R2 can be selected from at least one of amino, vinyl, methyl, epoxy, mercapto, and acryloxypropyl groups, and these groups have strong reactivity with different organic resins, and X is a hydrolyzable group.

[0095] The silane coupling agent includes at least one of an amino silane coupling agent, an epoxy silane coupling agent, an alkenyl silane coupling agent, a silane coupling agent containing a methacryloxy group, and a silane coupling agent containing a halogen. Exemplarily, the silane coupling agent is selected from at least one of vinyl triethoxysilane, epoxy silane, methacryloxy silane, γ-glycidyloxypropyl trimethoxy silane, γ-methacryloxypropyl trimethoxy silane, mercaptopropyl trimethoxy silane, dodecyl trimethoxy silane, or methylphenyl dimethoxy silane.

[0096] The hydrolysis reaction mechanism of silicon-containing compounds is shown in the following formula (a):

[0097]

[0098] The silicon-containing compound first undergoes a hydrolysis reaction, and then undergoes a dehydration condensation reaction to form an oligomer, and then reacts with the hydroxyl group in the organic resin, thereby producing a coupling effect with the organic resin.

[0099] Furthermore, the Si-OH group formed by the hydrolysis of the silicon-containing compound can react with the Si-OH formed by the hydrolysis of the silane coupling agent to form a Si-O-Si chemical bond. Through dehydration condensation, the silicon-containing compound in the electrophoretic medium can react chemically with the silane coupling agent in the adhesive used to form the sealing layer, so that the bonding layer has a Si-O-Si chemical bond. In the actual test process, the sealing layer 30 can be peeled off from the electrophoretic display layer 20, and the surface of the sealing layer 30 close to the electrophoretic display layer 20 can be analyzed by infrared spectroscopy to measure the Si-O-Si chemical bond. The bonding layer formed by the chemical reaction can enhance the interface connection force between the electrophoretic medium and the sealing layer formed by the adhesive, and improve the liquid-liquid interface bonding strength.

[0100] In some embodiments, the silane coupling agent can also chemically react with the organic group and the inorganic group to form a chemical bond or physical adsorption, so that the sealing layer and the first substrate can also form a strong bond, improve the bonding strength, and increase the structural reliability of the display device. Specifically, the organic functional group R2 in the silane coupling agent can form a chemical bond with the substrate (such as plastic).

[0101] It should be noted that the second additive in the electrophoretic medium and the third additive in the sealing layer may also be the same, for example, both are silane coupling agents. The second additive reacts with the third additive to form a Si-O-Si chemical bond, so that a bonding layer 50 is formed between the electrophoretic medium and the adhesive (sealing layer), thereby improving the bonding strength of the liquid-liquid interface. The silane coupling agent in the sealing layer can also form a strong bond between the sealing layer and the second substrate, thereby improving the bonding strength and increasing the structural reliability of the display device.

[0102] Figure 5 This is a schematic diagram of the structure of another display panel provided in the third embodiment of the present application. Different from the first embodiment, Figure 5 As shown, the display panel further includes a hardening layer 60 located between the electrophoretic medium 22 and the sealing layer 30 . The hardening layer 60 may be located on a surface of the sealing layer 30 close to the electrophoretic display layer 20 , or may be a part of the sealing layer 30 .

[0103] The formation mechanism of the hardened layer 60 is similar to that of the bonding layer 50. During the packaging process, the adhesive is coated on the surface of the electrophoretic display layer, and the adhesive is cured to form the sealing layer 30. The additives in the electrophoretic medium can undergo a cross-linking reaction with the active groups on the prepolymer in the adhesive to form the hardened layer 60, thereby improving the weather resistance of the packaging adhesive to the electrophoretic medium and enhancing the stability of the packaging structure.

[0104] In some embodiments, the electrophoretic medium 22 includes a fourth additive, and the density of the fourth additive is lower than the density of the electrophoretic medium. Due to the lower density of the fourth additive, the fourth additive can float to the liquid surface of the electrophoretic medium, and a raised interface is formed in the middle of the electrophoretic medium liquid surface, so that the contact area between the adhesive covering the electrophoretic medium and the cofferdam is increased, thereby improving the bonding strength between the sealing layer and the cofferdam.

[0105] In some embodiments, the hardening layer 60 is formed by a cross-linking reaction between a fourth additive and the sealing layer 30, the fourth additive has a first active group, and the adhesive used to form the sealing layer 30 has a second active group, and the first active group and the second active group are independently selected from at least one of a carbon-carbon double bond, a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an aldehyde group, and a halogenated alkyl group.

[0106] In some embodiments, the fourth additive includes a multifunctional acrylic monomer having a density lower than 1.2 g / mL. Specifically, the multifunctional acrylic monomer includes at least one of ethylene glycol diacrylate (EGDA, 1.1 g / mL), 1,6-hexanediol diacrylate (HDDA, 1.01 g / mL), 1,4-butanediol diacrylate (BDDA, 1.051 g / mL), trimethylolpropane triacrylate (TMPTA, 1.108 g / mL), ethoxylated trimethylolpropane triacrylate (TMPEOTA, 1.098 g / mL), tetraethylene glycol dimethacrylate (1.082 g / mL), trimethylolpropane trimethacrylate (1.06 g / mL), propoxylated trimethylolpropane triacrylate (1.054 g / mL), propoxylated glycerol triacrylate (1.11 g / mL), and pentaerythritol triacrylate (1.18 g / mL).

[0107] In some embodiments, the mass percentage of the fourth additive in the electrophoretic medium is 0.1% to 1%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0108] In some embodiments, the first active group of the fourth additive undergoes a cross-linking reaction with the second active group in the adhesive, and through Fourier transform infrared spectroscopy (FTIR) testing, the surface of the sealing layer close to the electrophoretic display layer has intermolecular hydrogen bonds, that is, the hardened layer has intermolecular hydrogen bonds.

[0109] In some embodiments, the material of the sealing layer 30 may include polyacrylate and / or polymethacrylate, and the number average molecular weight of the adhesive is 200,000 to 1.5 million. Figure 6aAs shown, the molecular chain of polyacrylate has active groups such as hydroxyl and carboxyl, and the fourth additive multifunctional acrylic monomer also has active groups, which can be cross-linked with the active groups on the molecular chain of polyacrylate to produce hydrogen bonding.

[0110] In some embodiments, the material of the dam 21 and the first substrate 10 is a polymer having polar groups, such as polyesters and polyamides. These polymers all contain polar groups. For example, the material of the sealing layer 30 is polyacrylate. Figure 6b As shown, the sealing layer 30 is connected to the cofferdam 21 and the first substrate 10 through the dipole effect, which can improve the bonding force of the sealing layer 30 to the cofferdam and enhance the interface bonding force between the sealing layer 30 and the first substrate 10 .

[0111] In some embodiments, the Shore hardness of the hardened layer is greater than 50HA, and may be specifically 51HA, 55HA, 58HA, 60HA, 65HA, 70HA, 80HA or 90HA, etc. Of course, it may also be other values ​​within the above range, which is not limited here.

[0112] Figure 7 A structural diagram of another display panel provided in the fourth embodiment of the present application is shown in FIG. Figure 7 As shown, the orthographic projection area of ​​the top surface of the cofferdam 21 away from the second substrate 40 on the second substrate 40 is larger than the orthographic projection area of ​​the bottom surface of the cofferdam 21 close to the second substrate 40 on the second substrate 40 .

[0113] The accommodating cavity formed by the cofferdam 21 of this structure is wide at the top and narrow at the bottom, so that the side wall of the cofferdam 21 can be inclined, thereby increasing the contact area between the side wall of the cofferdam and the sealing layer and enhancing the bonding strength between the sealing layer and the electrophoretic display layer.

[0114] Figure 8a This is a structural diagram of another display panel provided in Embodiment 5 of the present application. Figure 8b A cross-sectional transmission electron microscope image of another display panel provided in Example 5 of the present application; Figure 8a and Figure 8b As shown, the orthographic projection area of ​​the top surface of the cofferdam 21 away from the second substrate 40 on the second substrate 40 is smaller than the orthographic projection area of ​​the bottom surface of the cofferdam 21 close to the second substrate 40 on the second substrate 40. In this case, Figure 8b As shown, under the action of the additive in the electrophoretic medium 22, the electrophoretic medium can form a convex interface, and within the range of a single accommodating cavity defined by the cofferdam, the angle a between the surface of the sealing layer 30 sealing the accommodating cavity and the side wall of the cofferdam 21 can be maintained less than 90°.

[0115] Fig. 9 Schematic diagram of a display device provided in an embodiment of the present application. Fig. 9 As shown, the display device includes the display panel 100 provided in the above embodiment. Exemplarily, the display device can be a mobile phone, a computer, a television, a car display, a wearable electronic device, a display screen of various smart devices, etc.

[0116] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0117] Example 1

[0118] A method for preparing a display device comprises the following steps:

[0119] (1) A first substrate (PET substrate) and a second substrate (glass substrate) are taken. A first electrode is provided on the surface of the first substrate, and a second electrode is provided on the surface of the second substrate. The first electrode and the second electrode are indium tin oxide.

[0120] (2) The dam is mounted on the surface of the second substrate provided with the second electrode by using an adhesive.

[0121] (3) Filling the electrophoretic medium into the multiple accommodating cavities of the cofferdam to form an electrophoretic display layer.

[0122] (4) An adhesive is coated on the surface of the electrophoretic display layer, with the coating thickness controlled to be 15 μm, and the first substrate is covered on the adhesive, and is placed under ultraviolet light for photocuring for 30 minutes to obtain a display panel.

[0123] The adhesive used in the embodiment of the present application includes an acrylate prepolymer, a photoinitiator, a crosslinking agent and a conductive material. In the specific preparation process, 52 parts by mass of isooctyl acrylate (EHA), 35 parts by mass of isobornyl acrylate (IBOA), 12 parts by mass of hydroxyethyl acrylate (HEA), 1 part by mass of acrylamide (AM) and 0.1 parts by mass of hydroxycyclohexyl phenyl ketone are fully mixed and placed under 365nm ultraviolet light to react until the viscosity is 3500cps to obtain an acrylate prepolymer. Then, the acrylate prepolymer is mixed with 0.1% by mass of the photoinitiator TPO, 0.1% by mass of the crosslinking agent HDDA, 2% by mass of the nano silver wire and the additives described in Table 1 to obtain a sealing layer adhesive.

[0124] According to the preparation steps of Example 1, examples and comparative examples were prepared, and the process parameters of each example are specifically shown in Table 1:

[0125] Table 1. Display panel preparation process parameters

[0126]

[0127]

[0128] [Peel strength test method of sealing layer]:

[0129] The base material, sealing layer and PET are bonded into a three-layer structure, cut into 120mm*25mm samples, and then attached to the glass (wiped clean with alcohol) with auxiliary adhesive. Then, a 2kg roller is used to repeatedly roll back and forth 3 times, and the sample is left to stand for 24 hours for a 180-degree peel test at a test speed of 300mm / min.

[0130] After testing, the adhesive strength of Examples 1 to 12 can all reach above 500gf / 25mm. It can be seen that due to the presence of the additive in the electrophoretic medium, the electrophoretic medium forms an interface that bulges toward the sealing layer, thereby increasing the contact area between the sealing layer and the cofferdam, thereby improving the bonding strength between the sealing layer and the cofferdam, and improving the bonding strength of the liquid-liquid interface contact, which is beneficial to improving the sealing of the flexible package.

[0131] According to the test data of Examples 1 to 4, it can be seen that with the change of the type and addition amount of the first additive in the electrophoretic medium, the bonding strength between the sealing layer and the cofferdam does not change much. Among them, the first additive in Example 2 is polydimethylsiloxane, which is an excellent silicone hydrophobic agent. Due to its small surface energy, a raised interface is formed on the surface of the electrophoretic medium. At the same time, since polydimethylsiloxane can react with the additive γ-glycidyloxypropyltrimethoxysilane in the adhesive to form a Si-O-Si bond and achieve chemical bonding, the interface connection force between the electrophoretic medium and the sealing layer formed by the adhesive can be further enhanced. The adhesive strength of the sealing layer reaches 752gf / 25mm, thereby improving the liquid-liquid interface bonding strength.

[0132] According to the test data of Examples 5 to 8, as the type of the second additive in the electrophoretic medium changes, the bonding strength between the sealing layer and the cofferdam does not change much; as the amount of the second additive added in the electrophoretic medium increases, the adhesive strength of the sealing layer also increases. Since the silicon-containing compounds in the second additive (such as poly (methyl hydrogen) siloxane, polydimethylsiloxane methyl sulfonate) can react with the additives γ-glycidyloxypropyl trimethoxysilane or γ-methacryloxypropyl trimethoxysilane in the adhesive to form Si-O-Si bonds, chemical bonding is achieved, thereby further enhancing the interface connection force between the electrophoretic medium and the sealing layer formed by the adhesive, and improving the liquid-liquid interface bonding strength.

[0133] According to the test data of Examples 9 to 12, when the fourth additive in the electrophoretic medium is a multifunctional acrylic monomer, due to the low density of the multifunctional acrylic monomer, it can float to the liquid surface of the electrophoretic medium, and the electrophoretic medium liquid surface forms a raised interface in the middle, so that the contact area between the adhesive covering the electrophoretic medium and the cofferdam becomes larger, thereby improving the bonding strength between the sealing layer and the cofferdam. At the same time, since the carbon-carbon double bond active groups of the multifunctional acrylic monomers provided in Examples 9 to 12 can cross-link with the carbon-carbon double bond active groups in the adhesive, the electrophoretic medium and the sealing layer are cross-linked to form a hardened layer, and the hardened layer has intermolecular hydrogen bonds, which can further improve the liquid-liquid interface bonding strength. The adhesive strength of the sealing layer of Examples 9 to 12 can reach more than 800gf / 25mm, which improves the bonding strength between the sealing layer and the cofferdam, improves the bonding strength of the liquid-liquid interface contact, and is beneficial to improving the sealing of the flexible package. Compared with Example 1, in Comparative Example 1, no additive was added to the electrophoretic medium, and it was difficult for the electrophoretic medium to form a raised interface, the contact area between the sealing layer and the cofferdam was reduced, and the bonding strength between the sealing layer and the cofferdam was reduced. Similarly, compared with Example 3, in Comparative Example 2, no additive was added to the electrophoretic medium, and it was difficult for the electrophoretic medium to form a raised interface, the contact area between the sealing layer and the cofferdam was reduced, and the bonding strength between the sealing layer and the cofferdam was reduced.

[0134] The applicant declares that the present invention illustrates the method and its core idea through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A display panel, characterized in that: include: A first substrate and a second substrate arranged opposite to each other; an electrophoretic display layer located between the first substrate and the second substrate; The electrophoretic display layer includes a cofferdam and a receiving cavity defined by the cofferdam, and an electrophoretic medium is arranged in the receiving cavity; A sealing layer located between the electrophoretic display layer and the first substrate; wherein, The electrophoretic medium includes a first additive, and the surface energy of the first additive is smaller than the surface energy of the electrophoretic medium.

2. The display panel according to claim 1, characterized in that: The electrophoretic medium forms an interface that bulges toward the sealing layer.

3. The display panel according to claim 1, characterized in that: The surface energy of the first additive is lower than 25 mN / m.

4. The display panel according to claim 1, characterized in that: The first additive is a hydrophobic material, and the mass percentage of the hydrophobic material in the electrophoretic medium is 0.01% to 1%.

5. The display panel according to claim 1, characterized in that: Also includes: a bonding layer, located between the electrophoretic medium and the sealing layer; The electrophoretic medium includes a second additive, the sealing layer includes a third additive, the bonding layer is formed by the reaction of the second additive and the third additive, and the bonding layer is located on a surface of the sealing layer close to the electrophoretic display layer.

6. The display panel according to claim 5, characterized in that: The second additive includes a silicon-containing compound, the third additive includes a silane coupling agent, and the bonding layer has a Si-O-Si chemical bond.

7. The display panel according to claim 6, characterized in that: The chemical formula of the silicon-containing compound is shown in Formula I below: In Formula I, X represents a hydrolyzable group, and R1 is selected from active groups capable of interacting with an organic resin; The general chemical formula of the silane coupling agent is R2-Si(OM)3, wherein R2 is selected from an organic group and OM represents a hydrolyzable alkoxy group.

8. The display panel according to claim 7, characterized in that: X is selected from a halogen atom, an alkoxy group, and an acyloxy group; R1 is selected from at least one of an amino group, a mercapto group, a vinyl group, an epoxy group, a cyano group, and a methylacryloyloxy group; R2 is selected from at least one of an amino group, a vinyl group, a methyl group, an epoxy group, a mercapto group, and an acryloxypropyl group.

9. The display panel according to claim 6, characterized in that: The mass percentage of the second additive in the electrophoretic medium is 0.01% to 1%, and the mass percentage of the third additive in the sealing layer is 0.05% to 1%.

10. The display panel according to claim 1, characterized in that: Also includes: a hardening layer, located between the electrophoretic medium and the sealing layer; The electrophoretic medium contains a fourth additive, the density of the fourth additive is lower than that of the electrophoretic medium, the hardened layer is formed by a cross-linking reaction between the fourth additive and the sealing layer, and the hardened layer is located on a surface of the sealing layer close to the electrophoretic display layer.

11. The display panel according to claim 10, characterized in that: The fourth additive has a first active group, and the adhesive used to form the sealing layer has a second active group. The first active group and the second active group are independently selected from at least one of a carbon-carbon double bond, a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an aldehyde group, and a halogenated alkyl group.

12. The display panel according to claim 10, characterized in that: The fourth additive includes a multifunctional acrylic monomer having a density lower than 1.2 g / mL.

13. The display panel according to claim 12, characterized in that: The multifunctional acrylic monomer includes at least one of ethylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, triethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and pentaerythritol triacrylate; the sealing layer includes polyacrylate and / or polymethacrylate.

14. The display panel according to any one of claims 10 to 13, characterized in that: The hardened layer has intermolecular hydrogen bonds.

15. The display panel according to any one of claims 10 to 13, characterized in that: The Shore hardness of the hardened layer is greater than 50HA.

16. The display panel according to claim 11, characterized in that: The material of the dam and the first substrate is a polymer having polar groups, and the sealing layer is connected to the dam and the first substrate through a dipole effect.

17. The display panel according to claim 1, characterized in that: Within the scope of a single accommodating cavity defined by the cofferdam, an angle between the sealing layer that seals the accommodating cavity and a side wall of the cofferdam is less than 90°.

18. The display panel according to claim 1, characterized in that: Within the scope of a single accommodating cavity defined by the cofferdam, an edge thickness H1 of the sealing layer that seals the accommodating cavity and a middle thickness H2 of the sealing layer satisfy: 1nm≤H1-H2≤100nm.

19. The display panel according to claim 1, characterized in that: The orthographic projection area of ​​the top surface of the cofferdam away from the second substrate on the second substrate is larger than the orthographic projection area of ​​the bottom surface of the cofferdam close to the second substrate on the first substrate.

20. A display device, characterized in that: The display device comprises the display panel according to any one of claims 1 to 19.